Soil fertility and rhizosphere microbiome affecting hydroxysafflor yellow A accumulation in safflower - Shen, Wenjie; Yang, Wanting; Qin, Shuwei; Liu, Yang; Li, Guojun; Zhang, Xia; Bao, Mingqiang; Lu, Yaqian; Sun, Kexin; Ma, Wei; Li, Hongbin; Ismayil, Asigul; et al. (Frontiers in Microbiology, 2026)
IntroductionSafflower (Carthamus tinctorius L.) is a prized medicinal species whose therapeutic value hinges on the abundance of bioactive metabolites. Accumulation of these metabolites are influenced by a range of environmental and edaphic factors, including soil physicochemical parameters, extracellular enzyme activities, composition and function of rhizosphere microbiome. However, how these factors individually and synergistically orchestrate the biosynthesis, transport, and ultimate storage of pharmaceutically active compounds within Safflower tissues remains unknown.MethodsHere, high-throughput amplicon sequencing coupled with comprehensive physiological profiling was employed to investigate soil characteristics, enzyme activities, and rhizosphere microbial communities of safflower across 36 soil samples collected at two distinct altitudes and two growth stages.ResultsThe effective component content was detected in 18 samples, and our results revealed that the safflower stigmas from the high- altitude site (YM) contained significantly elevated levels of hydroxysafflor yellow A (HSYA) compared to those from the lowland site (YF). Soils at the YM site exhibited markedly higher fertility, with available phosphorus, total nitrogen, and organic matter identified as key drivers of HSYA accumulation. Both sites showed high diversity and abundance in rhizosphere microbial communities, with Actinobacteria and Proteobacteria dominating the bacterial communities, and Ascomycota being the predominant fungal phylum.DiscussionTaken together, our findings show that soil properties, microbial communities, and climatic conditions work interactively to influence the buildup of bioactive compounds in safflower. These insights suggest that precise management of soil nutrients and the rhizosphere microbiome can improve medicinal safflower quality.